Studi Persepsi Mahasiswa UNIKOM terhadap Legalitas Akses Film melalui Situs Streaming Ilegal - Andri Sahata Sitanggang; Devarian Firmansyah; Muhamad Riski Kautsar; Naufal Hasya Mulyana (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
The rapid development of digital technology has had a significant impact on various aspects of human life, including the distribution and consumption of entertainment content. One form of entertainment that has undergone a major transformation is film, where the existence of digital platforms has made access to various film titles increasingly easy, fast, and practical. The presence of official, legal streaming services offers a comfortable viewing experience and supports the sustainability of the film industry. However, on the other hand, this phenomenon has also given rise to a new problem, namely the increasing practice of accessing films through illegal streaming sites that are easily found on the internet. The use of illegal streaming sites certainly has various consequences, both legal, ethical, and economic. From a legal perspective, such actions clearly violate copyright, which should be protected by law. From an economic perspective, this illegal practice is detrimental to many parties, from film producers and distributors to the state, which loses potential revenue. However, the reality on the ground shows that the majority of the public, especially students, still frequently use illegal sites due to considerations of free access, the availability of the latest films, and ease of use. Based on this phenomenon, this study focuses on evaluating the perceptions of students at the Indonesian Computer University (UNIKOM) regarding the legality of using illegal streaming sites. The research was conducted using a descriptive quantitative approach, with primary data obtained through questionnaires distributed to 30 students from various study programs. The results are expected to provide insight into students' level of legal awareness and the factors influencing their choices regarding accessing films through legal and illegal channels. These findings are also expected to provide input for stakeholders in formulating educational and outreach strategies regarding the importance of respecting copyright.